Tourism flows, territorial capital and cycling. Andalusia as a model of emerging cycle tourism destination. - Fernández-Latorre, Francisco M. (Revista de Estudios Andaluces, 2015)
The article analyzes the relationships between territorial capital and cycle tourism, and more specifically, the interconnections that exist between tourism flows, coastline length, assets of cultural interest, protected natural areas and population; as well as their influence on cycle tourism. To this end, a linear correlation analysis was conducted amongst Spanish Autonomous Communities. Furthermore, particular conditions of territorial capitals were identified by using a number of indicators, as well as existing sectorial planning instruments and global market trends. A potential market structure is outlined by contrasting tourist profiles according to the percentage of total number of journeys by bicycle in the tourist source community and generated tourism flows. Finally, a multidimensional model for cycle tourism is proposed, a set of conclusions and recommendations for assessment, planning and integrated management of the sector are defined